Synopsis of biological data on the grass carp : - Shireman, Jerome V. (FAO, 1983)
This synopsis has been prepared in view of the growing importance of Ctenopharyingodon idella for aquaculture and for weed control which has resulted in its widespread introduction into waters throughout the world.